Traditional ecological knowledge and non-food uses of stingless bee honey in Kenya's last pocket of tropical rainforest - Madeleine Héger; Pierre Noiset; Kiatoko Nkoba; Nicolas J. Vereecken (BMC, 2023)
Abstract Background Stingless bee honey (SBH) is a natural remedy and therapeutic agent traditionally used by local communities across the (sub-)tropics. Forest SBH represents a prime non-timber forest product (NTFP) with a potential to revitalize indigenous foodways and to generate income in rural areas, yet it is also used in a variety of non-food contexts that are poorly documented in sub-Saharan Africa and that collectively represent a significant part of the local traditional ecological knowledge (TEK) passed on across generations. Documenting TEK of local communities in African tropical forests facing global change is a pressing issue to recognize the value of their insights, to evaluate their sustainability, to determine how they contribute to enhancing conservation efforts, and how TEK generally contributes to the well-being of both the natural environment and the communities that rely on it. This is particularly important to achieve in Kenya's only tropical rainforest at Kakamega where SBH production and non-food uses have evolved and diversified to a remarkable extent. Methods We used ethnographic techniques and methods, including semi-structured questionnaires and recorded interviews. We used snowball sampling, a non-probability sampling method where new interviewees were recruited by other respondents, to collectively form a sample consisting of 36 interviewees (including only one woman). Results Our results indicate that local communities in Kakamega were able to discriminate between six different and scientifically recognized stingless bee species, and they provided detailed accounts on the species-specific non-food uses of these SBH. Collectively, we recorded an array of 26 different non-food uses that are all passed on orally across generations in the Kakamega community. Conclusion Our results uncover the vast and hitherto unexpected diversity of TEK associated with SBH and pave the way for a systematic survey of SBH and their non-food uses across a network of communities in different environments and with different cultural backgrounds in the Afrotropics. This, along with parallel and more in-depth investigations into honey chemistry, will help develop a comprehensive understanding of SBH, offering insights into holistic ecosystem management, resilience and adaptation while in the mid- to long-term promoting cross-cultural exchanges and pathways for the revitalization of cultural practices and traditions.